Postmortem Neuroimaging of Cetacean Brains Using Computed Tomography and Magnetic Resonance Imaging - Kot, Brian C. W.; Tsui, Henry C. L.; Chung, Tabris Y. T.; Lau, Amy P. Y. (Frontiers in Marine Science, 2020)
Postmortem computed tomography (PMCT) and postmortem magnetic resonance (PMMR) imaging (PMMRI) have been applied to provide vital or additional information for conventional necropsy, along the pioneering virtopsy-driven cetacean stranding response program in Hong Kong waters. It is common for stranded carcasses to become badly degraded and susceptible to rapid cerebral autolysis and putrefaction. Necropsy on decomposed brains with limited sample analysis often defy a specific diagnosis. Studies on PMMR neuroimaging have focused on neuroanatomy and brain morphology in freshly deceased or preserved specimens. Moreover, the literature is devoid of any reference on the potential value of PMMRI examination of decomposed cetacean brains. To that end, this project evaluated the benefits of PMMR neuroimaging in situ in decomposed carcasses in comparison to PMCT. A total of 18 cetacean carcasses were studied by PMCT and PMMRI examinations. Anatomical brain structures and visible brain pathologies were evaluated and scored using Likert-scale rating. Intracranial gas accumulation was clearly depicted in all cases by all radiological techniques. Other features were more clearly depictable in PMMRI than in PMCT images. Results of this study indicated that superiority of PMMRI compared to PMCT increased with advanced putrefaction of the brain. The preservation of structural integrity was presented by PMMRI due to its superior capability to evaluate soft tissue. Brain PMMRI should be incorporated in postmortem investigation of decomposed stranded cetaceans.